Does participatory farmer-to-farmer training improve the adoption of sustainable land management practices?. (September 2021) - Kansanga, Moses Mosonsieyiri; Bezner Kerr, Rachel; Lupafya, Esther; Dakishoni, Laifolo; Luginaah, Isaac
Abstract: Human-induced land degradation currently threatens the livelihoods of over 3 billion people globally. While Sustainable Land Management (SLM) has emerged as a widely accepted approach for addressing land degradation in agroecosystems, the use of SLM practices remains low among smallholder farmers. Empirical research points to the potentially beneficial role of participatory farmer-to-farmer (F2F) training and knowledge sharing in improving SLM in resource-poor contexts. Drawing theoretical insights from social learning and using cross-sectional data from an agroecology intervention with smallholder farming households in Malawi (n = 609 farming households, comprising 463 households that received F2F training in agroecology and 146 households that did not receive F2F training), we examine the association between participatory agroecology training and the adoption of SLM practices. Findings from tobit regression analysis show that F2F training was positively associated with the use of SLM practices (β = 0.04 p < 0.05) two years following the intervention after accounting for demographic, agricultural and socioeconomic factors. These findings contribute to a growing body of literature that demonstrates the potential of participatory F2F training to improve the uptake and maintenance of SLM technologies. In the context of resource constraints and the associated low agricultural extension in sub-Saharan Africa, participatory F2F training may offer a cost-effective way to reach a wide range of smallholder farmers to promote the use of SLM practices. Highlights: Farmers with F2F agroecology training were significantly more likely to use SLM. F2F helps sustain impacts: farmers used SLM practices 2+ years after intervention. Participatory F2F agroecology is viable areas of high land degradation.